Addressing adults with adverse childhood experiences requires a team approach. (September 2019) - Valeras, Aimee Burke; Cobb, Erin; Prodger, Mark; Hochberg, Erica; Allosso, Lucy; VandenHazel, Haley
Objective: The primary care office is an ideal setting to identify and address adverse childhood experiences, which is a strong predictor of chronic health outcomes and morbidity. This study sought to understand the experiences of primary care from the perspective of patients who experienced trauma. Method: Purposive sampling was used to select eligible and interested participants who identify a high adverse childhood experience score at a residency-based community health center, which offers integrated behavioral health services in primary care. Semistructured in-depth interviews conducted by doctoral-level behavioral health clinicians were audio-recorded, transcribed, and analyzed thematically. Results: Subjects ( n = 6) described aspects of medical setting, including removal of clothing or physical touch, that trigger their past trauma, which often resulted in maladaptive stress responses. Subjects also reported sensing when their complexity resulted in negative interpersonal dynamics between team members, and they described fearing abandonment from their team during these heightened stress states. The behavioral health clinician on the health care team served as an advocate, enhanced trust, and allowed for increased continuity and access to care. Conclusions: Given the role of adverse childhood experiences in health outcomes and the results of this study, incorporating a trauma-informed approach is essential to treating patients with adverse childhood experiences. We propose that integrating mental health professionals into primary care settings better serves patients with trauma histories.